Teachers' Learning - Wallace, J. author. aut Link
IX, 193 p.
Keywords: Teachers' Learning: Stories of Science Education is aimed at science educators who wish for a deeper understanding of how teachers learn to teach science and the role of stories in reporting science education research. It is a fascinating look at the knowledge teachers have and use, how context influences teachers' work, and the role of reflection and collaboration in teachers' learning. At the core of each chapter is a story or group of stories written by or about teachers. These stories serve as a form of data to build a set of arguments about how science teachers grow and the possibilities for change in teaching. This book is designed for all those involved in the science teaching enterprise. Pre-service teachers, graduate students and science education researchers are invited to utilise both the findings about teachers' learning and the research processes employed to develop those findings.